2021
DOI: 10.46474/jds.910234
|View full text |Cite
|
Sign up to set email alerts
|

Insight into a Personalized Procedure of Design in Concept Generation by the Students in Architecture Thesis Projects

Abstract: This paper analyses the predominant trend between the students to follow, frame, and develop a concept in the architectural thesis design. The research targets to question how the students derive their inspiration from diverse sources and influencers into the architectural design concept. The research methodology was based on semi-structured questionnaires with Likert scale questions to analyse and interpret data through the Chi-Square test in SPSS software. The findings revealed that first, the students prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(56 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…The students preferred to exemplify the studies through images and graphics to refer to the precedents studies as the lessons learnt without differentiation between of the research 'in or for' architecture that advocated by Frayling (1993). It means that the students applied different approaches to discover their own theoretical framework than a structured research process (Tafahomi, 2021a). They also were so interested in precedents studies than theoretical topics (Borden & Ray, 2006) in the presentation that made their works more graphical than critical.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The students preferred to exemplify the studies through images and graphics to refer to the precedents studies as the lessons learnt without differentiation between of the research 'in or for' architecture that advocated by Frayling (1993). It means that the students applied different approaches to discover their own theoretical framework than a structured research process (Tafahomi, 2021a). They also were so interested in precedents studies than theoretical topics (Borden & Ray, 2006) in the presentation that made their works more graphical than critical.…”
Section: Discussionmentioning
confidence: 99%
“…The students learnt continuously through their own presentation and communication to improve the theoretical framework that this achievement of the research has been less discussed by the studies (Bloomberg & Volpe, 2019;Borden & Ray, 2006;Tafahomi, 2021a). Although the studies revealed and advocated a linear process between the studies and the students to select, integrate, and present the results of the studies, the findings highlighted that the students were learnt through following the peer-learner in the presentation to borrow data and styles for effective communication (Frey, 2018;Tafahomi, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations